Emergency aid for self-employed in the COVID-19 pandemic: A flash in the pan? - Jörn Hendrich Block; Alexander Kritikos; Maximilian Priem; Caroline Stiel (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
The self-employed are among those facing the highest probability of strong income losses during the COVID-19 pandemic. Governments in many countries introduced support programs to support the self-employed, including the German federal government, which approved a exteuro50bn emergency aid program at the end of March 2020 offering one-off lump-sum payments of up to exteuro15,000 to those facing substantial revenue declines. In this contribution, we investigate the impact of this program using a real-time online-survey data with a total of more than 20,000 observations. We employ propensity score matching, making use of a rich set of variables that influence selection into the treatment and the outcome variable, the subjective survival probability. We observe that the emergency aid program had significant effects, with the subjective survival probability of self-employment being moderately increased. We further reveal important effect heterogeneities with respect to education, risk tolerance, and industries. We also observe positive effects only among those whose application was processed within a few days. Lastly, the positive effect on the survival probability is fading out already two weeks after the emergency aid was granted. Our findings have important policy implications for the design of such support programs in the course of this crisis.
Keywords: C14; H43; L25; L26; J68; 330; Self-Employment; Emergency Aid; Treatment Effects; COVID-19; Entrepreneurship